1981
DOI: 10.1037/0096-1523.7.6.1340
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual processing strategies in the cross-modal transfer of form discrimination: A developmental study.

Abstract: Groups of Grad 1, high school students, and elderly subjects were tested for their ability to discriminate tactile forms. The performance of control subjects who received no prior training was compared with that of subjects who received prior visual training under normal viewing conditions (Vw), or prior visual training with special goggles restricting form perception to a series of part impressions (Vp). Both the visual and tactile versions of the task involved comparisons of standard figures matched either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Some authors tested visual-to-tactual recognition or tactual-to-visual recognition (Oscar-Berman et al, 1990; Norman et al, 2006), others did temporal order judgment tasks with or without distractors in the same or other modality (Poliakoff et al, 2006a,b), others did the Fitts’ task (Temprado et al, 2013) and a tactual transfer task (Coté and Schaefer, 1981). Other authors looked at the effects of the suppression or disturbance of the input of a modality; Brodoehl et al (2015) investigated the changes in somatosensory detection threshold when participants opened and closed their eyes; Strupp et al (1999) investigated the effects of somatosensory perturbation using dorsal muscle vibration on the performance in a task where participants were asked to move a laser spot to the position they perceived as straight ahead.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors tested visual-to-tactual recognition or tactual-to-visual recognition (Oscar-Berman et al, 1990; Norman et al, 2006), others did temporal order judgment tasks with or without distractors in the same or other modality (Poliakoff et al, 2006a,b), others did the Fitts’ task (Temprado et al, 2013) and a tactual transfer task (Coté and Schaefer, 1981). Other authors looked at the effects of the suppression or disturbance of the input of a modality; Brodoehl et al (2015) investigated the changes in somatosensory detection threshold when participants opened and closed their eyes; Strupp et al (1999) investigated the effects of somatosensory perturbation using dorsal muscle vibration on the performance in a task where participants were asked to move a laser spot to the position they perceived as straight ahead.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Gescheider, Edwards, Lackner, Bolanowski, and Verrillo (1996) also reported a decline in sensitivity with age, whereas there was no effect of age on suprathreshold intensitive difference limens (DLs). A few notable studies have shown similar declines in performance in complex measures of tactile pattern processing, such as haptic or form exploration (Axelrod & Cohen, 1961;Coté & Schaefer, 1981;Kleinman & Brodzinsky, 1978), spatial acuity (Stevens, 1992), or temporal processing (Van Doren, Gescheider, & Verrillo, 1990). The underlying cause of the progressive loss has usually been attributed to physiological changes in the skin itself (e.g., Steinberg & Graber, 1963;Stevens, 1992;Verrillo, 1979) or neurological factors (Lindblom & Verrillo, 1979;Mirsky, Futterman, & Broh-Kahn, 1953;Wahren & Torebjork, 1992).…”
mentioning
confidence: 99%
“…In other words, the subject is not able to process the necessary information in any kind of usable form (cf. Cote & Schaefer, 1981). …”
Section: Transfer Of Trainingmentioning
confidence: 99%